(untitled) (Revista Brasileira Multidisciplinar, 2024)
Antimicrobial peptides are found in a wide variety of living organisms, including medicinal plants. These are natural molecules and with activity against pathogenic and phytopathogenic bacteria. With growing microbial resistance heading into the post-antibiotic era, the exploration of these peptides by alternative methodologies using bioinformatics tools has become promising. The objective of this work was to prospect antimicrobial peptides from medicinal plants using bioinformatics tools for biotechnological applications. To verify the state of the art, searches were carried out for scientific articles in academic journals from 2018 to 2022. Bioinformatics analyzes were conducted in protein and peptide databases, NCBI, Uniprot/Swiss-Prot, CAMP and APD3 with the terms of the ten families of antimicrobial peptides. Predictions of physical-chemical and toxicity characteristics were performed using Expasy and ToxinPred software, respectively. Many scientific articles were obtained with the research theme, demonstrating the great relevance of the area. The peptides with the highest number of deposits in the databases of medicinal plants were defensins, heveins and knotins. One hevein stood out for its stability in its structure and did not show toxicity to mammalian cells. The study of these peptides can be useful in the design of synthetic molecules that can be exploited for biotechnological applications.